Increased von Willebrand factor levels in polycythemia vera and phenotypic differences with essential thrombocythemia - Sacco, Monica (Res Pract Thromb Haemost, 2020)
BACKGROUND: Acquired von Willebrand factor (VWF) deficiency was described in Philadelphia‐negative myeloproliferative neoplasms, especially in essential thrombocythemia (ET). VWF phenotype in contemporary patients with polycythemia vera (PV) remains less explored. OBJECTIVES: To characterize the VWF phenotype in PV and to compare VWF phenotype in PV with matched healthy subjects and ET patients. PATIENTS/METHODS: We studied 48 PV patients, treated according to current recommendations (hematocrit ≤ 45%, on low‐dose aspirin prophylaxis); 48 healthy and 41 subjects with ET, all sex, age, and blood group matched. We measured VWF antigen, activity, multimeric pattern, ADAMTS‐13, and factor VIII (FVIII) antigen. RESULTS: In patients with PV, VWF antigen and activity were significantly higher than in healthy subjects (antigen: 119[96‐137] vs 93[79‐107] IU/dL; activity: 114[95‐128] vs 90[79‐107] IU/dL, respectively, medians and interquartile, P < 0.01), with normal multimeric distribution. ADAMTS‐13 levels were similar between patients with PV and healthy subjects. FVIII levels were higher in PV than in healthy subjects (141[119‐169] versus 98[88‐123] IU/dL, respectively, P < 0.01). By multivariable analysis, JAK2‐p.V617F allelic burden, erythrocyte count, and male sex significantly predicted VWF antigen and activity levels. As compared to patients with ET, patients with PV showed similar VWF antigen levels but approximately 40% higher activity (79[49‐104] vs 112[93‐125] IU/dL, respectively, P < 0.01). CONCLUSIONS: Patients with PV show increased VWF and FVIII levels, predicted by JAK2‐p.V617F burden and erythrocyte count. At variance with ET, acquired VWF defect was not observed in PV. High VWF/FVIII levels may sustain the thrombotic diathesis of PV and may be investigated as biomarkers for risk stratification.